Financing Businesses for Sustainable Growth: Economic, Social, and Environmental Drivers With A Gender Approach - Santos-Jaén, José Manuel; Iglesias-Sánchez, Patricia Pilar; Nataliia, Meda; De-las-Heras-Jambrino, Carlos (Wiley, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) practices and financial performance, incorporating a gender perspective. While ESG frameworks enhance investment attractiveness, the role of female leadership remains underexplored. Using a sample of EuroStoxx 300, the data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study assessed financial capital, investment attractiveness, and sustainability performance with gender representation as a moderating variable. The results confirm a positive relationship between financial capital and economic/social efficiency, while environmental efficiency presents mixed effects. Female board representation strengthens the link between investment attractiveness and financial capital. These findings contribute to the literature by integrating gender as a strategic factor in ESG-financing research and highlight the practical implication that companies should promote gender-diverse leadership to maximize the financial and strategic benefits of sustainable practices.
Keywords: Mercado financiero; Desarrollo económico y social; Igualdad de género; Gobierno de la empresa; Desarrollo sostenible; Efficiency; Environmental Social and Governance (ESG); Financial capital; Investment attractiveness; Sustainability; Women on board